2015
DOI: 10.2112/jcoastres-d-13-00087.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea Wave Parameters Prediction by Support Vector Machine Using a Genetic Algorithm

Abstract: Elbisy, M.S., 0000. Sea wave parameters prediction by support vector machine using a genetic algorithm. Journal of Coastal Research, 00(0), 000-000. Coconut Creek (Florida), ISSN 0749-0208.The prediction of sea wave parameters is important for the planning, design, and operation of coastal and ocean structures. Many empirical methods, numerical models, and soft computing techniques for wave parameter forecasting have been investigated, but such forecasting is still a complex ocean engineering problem. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In the paper, we select the radial basis kernel function as the kernel function in the LSSVM model to obtain the optimal solutions due to its strong nonlinear mapping ability and wide convergence domain (Min and Lee, 2005;Altınel et al, 2015;Elbisy 2015;Farzan et al, 2015):…”
Section: Lssvmmentioning
confidence: 99%
“…In the paper, we select the radial basis kernel function as the kernel function in the LSSVM model to obtain the optimal solutions due to its strong nonlinear mapping ability and wide convergence domain (Min and Lee, 2005;Altınel et al, 2015;Elbisy 2015;Farzan et al, 2015):…”
Section: Lssvmmentioning
confidence: 99%
“…Dibike et al [47] described the advantages that the radial basis function has over other kernels. Moreover, several studies [36,48,49] have demonstrated the superior capability of the radial basis function for hydrologic and wave forecasting. Therefore, this study used the radial basis function kernel with a parameter γ as the kernel function:…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…Mahjoobi and Mosabbeb [35] used an SVM to simulate the significant wave height for Lake Michigan by using current and previous wind speed data as inputs. Elbisy [36] combined an SVM and a genetic algorithm to predict the significant wave height, wave direction, and peak spectral period in a coastal zone near the Nile delta.…”
Section: Introductionmentioning
confidence: 99%
“…And surface settlement has been effectively controlled. Specific tunneling parameters are shown in Table3 and Table4 [5][6][7]. According to the geological and environmental conditions of Chengdu subway, the main role of the foam in EPB shield tunneling is to reduce the mechanical wear of shield machine.…”
Section: Fig4 Working Principle Of Foaming Systemmentioning
confidence: 99%